Social and Object Attention Is Influenced by Biological Sex and Toy Gender‐Congruence in Children With and Without Autism. Issue 5 (4th December 2019) - Harrop, Clare; Jones, Desiree R.; Sasson, Noah J.; Zheng, Shuting; Nowell, Sallie W.; Parish‐Morris, Julia
Abstract : Emerging research suggests social attention in autism spectrum disorder (ASD) girls is enhanced relative to ASD boys but may also be affected by the type of social and nonsocial content presented. This study examined how biological sex and gender norms interact to influence visual attention in 79 school‐aged children observing scenes that included gender‐associated toys and actors of both sexes. Attention to social (faces) and object activity (hands with toys) stimuli was measured. Previously described distinctions between social attention in ASD boys and girls were replicated, with ASD girls looking more at faces than ASD boys. Irrespective of diagnosis, males and females attended more to actors that shared their same sex, and attended more to toys with gender‐associations that were consistent with their own sex, suggesting that social and object salience increases for children under sex‐consistent conditions. Importantly, ASD and typically developing (TD) children increased their gaze to faces when male actors were shown playing with female‐associated toys, suggesting that both groups of children are sensitive to societal messages about the acceptability of males playing with female‐associated toys. Our findings provide further evidence of heightened attention to faces in ASD girls relative to ASD boys, and indicate that social attention in ASD and TD children is influenced by who (male or female actor) and what (male‐ or female‐associated toy) is being observed. Collectively, these results present a nuanced profile of attention in ASD that adds to a growing body of research indicating subtle phenotypic differences in ASD girls that may impact identification, assessment, and intervention. Autism Res 2020, 13: 763–776 .. © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Sex differences observed in typical development may also be present in individuals with autism. In this study, we developed an eye‐tracking paradigm featuring videos of boys and girls playing with toys that varied in their gender associations. Attention to faces differed between autistic and non‐autistic children but was also influenced by the sex of the actor and gender‐association of toys. Autistic females demonstrated subtle attention differences that distinguished them from autistic males and may influence referral, diagnosis, and intervention.